2000
DOI: 10.1006/qres.1999.2119
|View full text |Cite
|
Sign up to set email alerts
|

The Full-Glacial Forests of Central and Southeastern Europe

Abstract: The presence of trees in central and southern Europe during the last full-glaciation has long been a matter of debate. A low but persistent presence of fossil tree pollen in central and southern European full-glacial paleoecological sequences has been interpreted either as representing long-distance pollen transport from southerly refuges or as representing in situ refugial populations. Here we present macroscopic charcoal results from 31 sequences located throughout Hungary that provide unequivocal evidence f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
365
1
24

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 446 publications
(413 citation statements)
references
References 38 publications
23
365
1
24
Order By: Relevance
“…As a result, it can be assumed that a refugia of temperate forest existed in the analysed region. These data support the earlier palaeoecological and biogeographic analyses [37,56,58,59,79,80,84,88] that more refugia existed in the southern border of the Northern Carpathians where temperate forest habitat and taxon survived the coldest stages of the Pleistocene.…”
Section: The Findings Of Malacological Studies In Light Of the New Rasupporting
confidence: 86%
See 2 more Smart Citations
“…As a result, it can be assumed that a refugia of temperate forest existed in the analysed region. These data support the earlier palaeoecological and biogeographic analyses [37,56,58,59,79,80,84,88] that more refugia existed in the southern border of the Northern Carpathians where temperate forest habitat and taxon survived the coldest stages of the Pleistocene.…”
Section: The Findings Of Malacological Studies In Light Of the New Rasupporting
confidence: 86%
“…In addition, numerous charcoal fragments of the so-called thermomesophylic deciduous trees were identified in the sample, pointing to the development of a mixed taiga containing locally such deciduous elements as oak (Quercus) and maple (Acer), for example. These Late Glacial charcoal pieces serve as clear evidence for the local presence of thermomesophylous deciduous arboreal elements in the Late Glacial woodland vegetation of the Carpathian foreland, corroborating the findings of former palynological and malacological studies, which indicated the presence of thermomesophylous woodland refugia in the southern foothills of the Subcarpathian region of the Carpathians [57][58][59][79][80][81][82][83][84][85].…”
Section: The Findings Of Palaeobotanical Studies In Light Of the New supporting
confidence: 70%
See 1 more Smart Citation
“…As stated in § 1, such discrepancies between these temperate species are in part related to the location of their glacial refugia that represent the starting points of the postglacial migrational process. Both fossil pollen (figure 3) and macrofossils (Willis et al 2000) indicate, for instance, that birch and alder (figure 3a,b) survived at higher latitudes than oaks (figure 3c), in areas where a supply of moisture was available from the summer melting of ice. Oak trees, on the other hand, were not able to survive in such areas during the last glacial maximum because they are not as cold tolerant as birch or alder.…”
Section: Different Species Different Historiesmentioning
confidence: 99%
“…Alternatively, other species, such as birches, pines, spruces or willows are cold tolerant and were apparently able to survive the LGM at much higher latitudes. In birches or willows, the fossil pollen record provides very little information on possible LGM refugia and on the fate of the populations after the LGM, and all reliable information might have to come from serendipitous finds of macrofossils (Willis et al 2000;Stewart & Lister 2001;Birks 2003). As we shall see, in the absence of a fossil record, it will be very difficult to make any inference from genetic data alone and it will be difficult to justify the use of a specific demographic model in coalescent-based inferences.…”
Section: Introductionmentioning
confidence: 99%